2022
DOI: 10.1053/j.jfas.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Validity and Minimal Important Change for the Modified Lower Extremity Functional Scale (LEFS) in Orthopedic Foot and Ankle Patients

Abstract: The lower extremity functional scale (LEFS) is a patient-reported outcome measure for lower extremity disorders. Aim of this study was to assess the longitudinal validity including responsiveness and test-retest reliability of the revised 15-item version, and to define the minimal important change (MIC) of the modified LEFS in a generic sample of orthopedic foot and ankle patients who underwent surgery. Responsiveness, effect size, and standardized response mean were measured by determining the score change be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The literature concerning the measurement properties of LEFS scores indicates that it is a reliable, valid, and responsive tool for assessing functional status in several populations with lower extremity musculoskeletal conditions (30). A recent study concerning LEFS showed suboptimal longitudinal validity in a generic sample of orthopedic foot and ankle patients (44).…”
Section: Modified Lefsmentioning
confidence: 99%
“…The literature concerning the measurement properties of LEFS scores indicates that it is a reliable, valid, and responsive tool for assessing functional status in several populations with lower extremity musculoskeletal conditions (30). A recent study concerning LEFS showed suboptimal longitudinal validity in a generic sample of orthopedic foot and ankle patients (44).…”
Section: Modified Lefsmentioning
confidence: 99%